Error Analysis of Retrieved Aerosol Optical Depth and Surface Reflectance due to the Azimuthal Angle Simplification of Atmospheric Functions - 劉建慧(Chien-Hui Liu) (TAO : Terrestrial, atmospheric, and oceanic sciences, 2004)
Using a simplified azimuthal angle assumption of atmospheric functions in the atmospheric correction model, such as Atmospheric CORrection model version 2 (ATCOR2) and Atmospheric CORrection model version 3 (ATCOR3) developed by Richter (1997) for Systeme Pour I'Observation dela Terre (SPOT) High Resolution Visible (HRV) data, can generate errors. This paper discusses the errors of retrieved surface reflectance and aerosol optical depth (AOD) due to such simplification. The results indicate that the relative error of retrieved surface reflectance can exceed 40% in the forward-scattering direction in hazy sky and that of retrieved AOD can be over 10% in the anti-solar direction in clear sky at the extreme 40% in the forward-scattering direction in hazy sky and that of retrieved AOD can be over 10% in the anti-solar direction inclear sky at the extreme view angle. Hence, the consideration of azimuthal angle dependence of atmospheric function is indispensable for the atmospheric correction model of SPOT HRV data, particularly in large view angles, e.g., larger than -21.5¢X (backward-scattering region) and 24.9¢X (forward-scattering region) in clear sky, and larger that -19.1¢X and 12.9¢X in hazy sky.